The effect of wear of petrol engine power brush cutters on their vibration exposure - László, H. E. (International Journal of Horticultural Science, 2007)
The matter of noise and vibration exposure has an accentuated emphasis in the environmental protection policy of the European Union. In practice, the focus is on the evaluation of noise -strain. The evaluation on human beings’ vibration-strain is in focus in recent years. At the Technical Department in Corvinus University of Budapest Faculty of Horticultural Sciences we evaluate in PhD training form the possible ways of alleviation and revealance of noise and vibration-strain in gardening devices and machineries. According to the latest development in gardening culture, small gardening machines are more and more widespread. There is a law in Hungary for the compulsory grass-cutting, especially on ’ragweed’ (Ambrosia elatior). Along highways, public territories, parks workmen at least six months are in charge to terminate these weed-crops meanwhile they are endangered by serious harmful effects. The operators of hand-held power tools are exposed comprehensive levels of hand-arm vibration at the tool-hand interface. Many studies indicate that extended exposure to mechanical vibration can induce degeneration of the vascular and sensioneural systems in the hand called hand-arm vibration syndrome (HAVS). The precise mechanism for the initiation and development of HAVS is unclear to date. Measurement and risk assessment of hand-transmitted vibration is mostly based on the guidelines and dose-response relationship provided in the ISO-5349 standard. These guidelines suggest that the magnitude, frequency, direction and duration of vibration exposure are the most important variables for the risk assessment of hand-arm vibration. This current study is focusing on brush cutters owned by one of the biggest caretaker company. These machines have similar brand and age but different in usage time. We inquired seven brush cutters through two years. The manufacturer repaid the vibration level of the new machines, but they doesn’t examine, whether extent of the vibration emission is changing for the proper use. We wanted to know that are there any differences between the values of vibration specification after certain time of usage. Is it possible to monitor the alternate movements on graphs according to the vibration sciences? By Ill octave band frequency and FFT analysis we can point at that these brush cutters can show differences in critical frequencies. These biases can influence the hand-arm system and its vibration-strain burdening.